COVID-19 in Patients with Primary Biliary Cholangitis - М. К. Prashnova; K. L. Raikhelson; N. V. Marchenko; S. M. Zakharenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of the study. To analyze the course of COVID-19 infection in patients with primary biliary cholangitis (PBC).Materials and methods. In a single-center retrospective study, survey and analysis of medical records of 144 patients with PBC was carried out.Results. All patients (n = 144) received basic therapy with ursodeoxycholic acid (UDCA), 5 of them received fibrates as well. Response to therapy (EASL criteria) was obtained in 30 people. Between March 2020 and March 2021, 50 patients (34.7 %) suffered COVID-19, with mean age of 58.8 ± 10.7 years, 16 of which were diagnosed with liver cirrhosis. Mild COVID-19 was observed in 34 (68 %) people, moderate course — in 14 (28 %), severe — in 2 (4 %), cases of extremely severe course were not recorded. 12 patients were hospitalized, 8 of which received oxygen therapy due to a decrease in SpO2 < 94 %, there was no need for the use of other methods of oxygen therapy in any case. The duration of hospitalization was 11.4 ± 5.7 days. There was a higher initial activity of serum alkaline phosphatase (1.8 ± 1.0 versus 1.7 ± 1.4 times of the upper limit of normal, M ± SD, p = 0.04) in patients with COVID-19 infection and lack of UDCA therapy effectiveness was more prominent (40 % vs. 19.1 % of cases, p = 0.04) compared with patients who did not have COVID-19. There were no significant differences in characteristics of the course of PBC (stage, response to therapy) and age in correlation with severity of the course of COVID-19. Among hospitalized patients and those in need of oxygen support, large proportion were older patients (58.3 % and 62.5 %, respectively) and patients with concomitant diseases (62.5 % and 75 %, respectively). Patients who hadn`t previously responded to UDCA therapy were more likely to require oxygen support compared to patients responding to basic therapy (p < 0.01).Conclusion. PBC is not a risk factor for severe COVID-19. A protective effect of UDCA in SARS-CoV-2 infection is possible, which requires further investigation.